Accessory and Participation in Crime in the Qur'an (Emphasizing the Method of Legal Interpretation) - Seyed Ahmad Mirkhalili; Morteza Motahari Fard; Morteza Tavakoli Mohammadi (آموزه‌های قرآنی)
Legal interpretation of the Quran is one of the methods of interdisciplinary study between the science of Law and the Holy Qur'an. According to the topic, the issues of the science of law and what is expected of the comprehensiveness, perfection and wisdom of the Holy Qur'an, can be offered some issues in the liberal arts in ideological view to the Qur'an, and can be obtained a platform for theorizing it. In this regard, the greatness and superiority of the Holy Qur'an to other scientific resources will be obtained the ability to expand the knowledge of rights based on the truth of Human and the world and etc. In this study, with the focus of this method, one of the issues of the science of Law under the title of participation and accessory in crime will be dealt with the expurgation of legal dimensions of the Holy Qur'an. The main result of this research is the introduction of verses including the concept of participation and accessory, which are often invoked to two or three verses of this field in articles and the prior and later books. Other results of the research include the separation of the abettor and accomplice in the crime from the perpetrator and the amount of punishment for each and the implementation and comparison with the jurisprudential and legal achievements. The research method in this depiction is to define the subject, identify the related verses, categorize them, apply the rules of contemplation and interpretation in it, legal analysis and ordering the achieved results.